Green finance cooperation as a means of facilitating the development of partnership between Belarus and China - Andrey A. Deryushev; Kai Zhen (Вестник Воронежского государственного университета: Серия экономика и управление, 2023)
Subject. Partnership between the Republic of Belarus and China has been developing very quickly lately. At the end of the 20th century, the world recognised the need for a transition to a new resource-saving economic model - the so-called green economy, which combines overall wellbeing, including employment, and reduced pressure on the environment. This was brought about by grave environmental problems resulting from the human economic activities and the understanding that intensive use of natural resources will in the long term lead to their exhaustion. Even if new deposits are found, their development will require a lot of time and financial resources. Studying the best practices of the developed countries and emerging economies in the area of green finance is of utmost importance for the further development of the partnership between Belarus and China. The focus of our study was the effect of green finance on China-Belarus relationships. The purpose of our study was to determine the development prospects of the China-Belarus partnership based on cooperation in the area of green finance. Methodology. In our study, we used general scientific methods, including analysis, generalisation, and comparison. Conclusions. The article presents a review of the history of the partnership between China and Belarus. A review of green finance in the Republic of Belarus demonstrated that it is still at the initial development stage. It also demonstrated that at the moment the green economy of the Republic of Belarus needs green investment from China. A review of green finance in China demonstrated its effective development, especially in the area of green energy. Based on the analysis, we determined the development prospects of China-Belarus partnerships based on green finance cooperation.